Impact of HPAI on Ghanaian rural poultry producers’ incomes - Birol, Ekin; Asare-Marfo, Dorene (International Food Policy Research Institute, 2008)
Poultry production is an important livelihoods activity in the rural areas of many developing countries. Several studies from African and Asian countries have found that poultry production significantly contributes to several livelihoods indicators of rural households, such as income, food and nutrition security, and intra-household gender equality. In the event of highly pathogenic avian influenza (HPAI) outbreaks and associated demand and supply shocks, therefore, it is expected that severe impacts will be experienced not only by large-scale commercial poultry producers, but also by small-scale poultry producers, who depend upon poultry for their livelihoods.